JURIDICAL REVIEW OF RIGHT OF ACCESS TO LAND FOR INDONESIAN WOMEN CITIZEN WHO ARE BOUND BY MIXED MARRIAGE LAW (CASE STUDY DECISION OF THE CONSTITUTIONAL COURT NUMBER: 69 / PUU XIII / 2015) - achmad sulchan; Nurmalia IW (UNISSULA, 2017)
ABSTRACTMixed marriages are marriages involving a race between nations, therefore, marriage is also subject to the principles applicable in the Indonesian Law and International Law. Mixed marriage has penetrated the whole of Indonesia . Notary role in making the deeds relating to pernjanjian marriage, inheritance etc.Dealing with the issue of marriage between men and women WNA WNA especially about women's access rights to land for the citizen and problems. Therefore, the authors take the title on the Juridical Review of the Acquisition of Land Rights for Women Bound citizen Mixed Marriage (Case Study No. Constitutional Court.69 / PUU XIII / 2015). The contents of the Constitutional Court about: Testing Law No. 5 of 1960 on the Basic Regulation and the Basic Agrarian Law No. 1 of 1974 on Marriage of the Constitution of the Republic of Indonesia th 1945.Dalam decision mentions the Applicant, Ny. Ike Farida an Indonesian citizen. Applicant is a woman who is married to a Japanese national men by a valid marriage and are registered in the District Office of Religious Affairs Makasar East Jakarta Municipality No. 3948 / VII / 1995, the Civil Registry Office Prop. DKI Jakarta as defined in the Marriage Reports Receipt No. 36 / KHS / AI / 1849/1995/1999 dated May 24, 1999. Related to marriage, the applicant does not have marital separation agreement treasures, never abandoned his Indonesian citizenship and disenfranchised here at home. Applicant want to buy Flats in Jakarta, after the keel, towers not being handed over, and even then the purchase agreement terminated unilaterally by the developer. Then formulated the problems are: 1) What is the procedure of acquiring land rights for women citizens who are bound intermarriage? 2). Constraints and solutions that arise in obtaining the Women's Land Rights for citizens who are bound Mixed Marriage (Case Study No. Constitutional Court.69 / PUU XII / 2015)? As this study is sociological or empirical, in which the authors conducted a study which examined at first was secondary data, then resumed research on primary data in the field, or to society, an interview with the National Land Agency, notary, and two female citizens who marry foreigners. And examine the rules relating to mixed marriages, prevailing in Indonesia. The results showed the conclusion that the Notary has an important role in helping clients about: procedures for securing land rights for the citizen who is married to foreigners, namely the reduction in the rights, for example, from Properties menjaiHakPakai, the reduction in the rights of land owners. Constraints faced is the problem of domicile for male foreigners who are married to the citizen, and a couple of mixed marriages between Indonesian citizens and foreigners do not make a marriage agreement during their marriage. The solution is that if the land area can be divided into 2: 1/2; 1/2 for the wife, the land was downgraded to a Right of Use by registering at BPN, and made a covenant marriage.